Problems and Challenges Faced by Married Students to Continue their Study at University Level - Tahira, Syeda Samina; Khan, Erum Aslam; Arif, Muhammad Irfan (Annals of Human and Social Sciences, 2023)
The purpose of the study was to find out the challenges for married women to continue education at university level. Present study was descriptive in nature. The study is significant in terms of exploring the root causes of different problems faced by womanish wedded scholars while antedating advanced education after marriage. Quantitative research methodology was used to collect data. All public and private sector universities in Province Punjab were the population of the study. Researcher used purposive sampling technique to select the sample from population. 75 students were the sample of this study. Self-designed questionnaire was used to collect the data from sample. The data were analyses by using descriptive and inferential statistical techniques. The analysis revealed that the married students faced very critical challenges at higher education in Pakistan. Among these challenges Academic Challenges, Social Challenges, Time Management challenges, Financial Challenges and Health Challenges were found to be common in the married students at higher education in Pakistan. The study has important practical implications in the field of higher education in Pakistan with the recommendations of some modifications and changes in the mechanism of higher education in Pakistan to facilitate the education of married women at higher education.